2005
DOI: 10.1200/jco.2005.06.208
|View full text |Cite|
|
Sign up to set email alerts
|

Drug-Metabolizing Enzyme Polymorphisms Predict Clinical Outcome in a Node-Positive Breast Cancer Cohort

Abstract: Combined genotypes at CYP3A4, CYP3A5, GSTM1, and GSTT1 influence the probability of treatment failure after high-dose adjuvant chemotherapy for node-positive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 24 publications
3
21
0
1
Order By: Relevance
“…Consistently with our observation, patients with low drug metabolizing genotypes with acute myeloid leukemia, esophageal cancer, lung cancer, or breast cancer exhibited reduced survival rates in some studies (39)(40)(41)(42). This might be attributable to a higher rate of toxicity-related deaths.…”
Section: ------------------------------------------------------------supporting
confidence: 88%
“…Consistently with our observation, patients with low drug metabolizing genotypes with acute myeloid leukemia, esophageal cancer, lung cancer, or breast cancer exhibited reduced survival rates in some studies (39)(40)(41)(42). This might be attributable to a higher rate of toxicity-related deaths.…”
Section: ------------------------------------------------------------supporting
confidence: 88%
“…In line with the present study of BC, previous investigations of Hodgkin's lymphoma, ovarian cancer, colorectal cancer, and even BC have also found the same improved survival rates when lymph node status was associated with polymorphic forms of GSTT1, GSTM1, and GSTP1 (Khedhaier et al, 2003;Huang et al, 2003;Hohaus et al, 2005;DeMichele et al, 2005;Beeghly et al, 2006;Holley et al, 2006;Kweekel et al, 2008;Kolwijck et al, 2009;Jones et al, 2009;Khrunin et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, Mathijssen et al (2004) showed that CYP3A4 phenotype, as assessed by midazolam clearance, is statistically significantly associated with irinotecan pharmacokinetics. With respect to the already described CYP3A genotypes, a combination of CYP3A4, CYP3A5, GSTM1 and GSTT1 genotypes was shown to influence the probability of treatment failure after high-dose adjuvant chemotherapy for node-positive breast cancer (DeMichele et al, 2005). Table 3 also shows other important anticancer agents metabolized by CYP3A4, including taxanes, vinca-alkaloids and new drugs such as imatinib and gefitinib.…”
Section: P450 Pharmacogenetics C Rodriguez-antona and M Ingelman-sundmentioning
confidence: 99%